Rest Area Taman Rahayu Tipe A di Ruas Tol Cimanggis Cibitung dengan Penerapan Arsitektur Bioklimatik - Michael Joseph Doren; Uras Siahaan; Sahala Simatupang (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
The construction of the Cimanggis–Cibitung Toll Road requires rest areas as supporting facilities for road users. The Taman Rahayu Type A Rest Area is designed with a bioclimatic architecture concept to utilize environmental potential and reduce conventional energy use. The design adapts to the local climate through natural ventilation and efficient lighting. The design takes into account environmental conditions, user needs, and local potential. Facilities provided include rest areas, gas stations, commercial areas, and green spaces. The study results show that the application of bioclimatic architecture can improve energy efficiency, user comfort, and have a positive impact on the environment. This rest area is expected to serve as an example for the development of similar facilities in the future.